2018
DOI: 10.1007/8904_2018_96
|View full text |Cite
|
Sign up to set email alerts
|

Pentosan Polysulfate Treatment of Mucopolysaccharidosis Type IIIA Mice

Abstract: As seen in other MPS animal models, subQ PPS treatment reduced plasma cytokine levels and macrophage infiltration in systemic tissues. ICV administration did not elicit these systemic effects. SubQ PPS administration also significantly impacted brain neuropathology, inflammation, and behavior. The effect of early subQ treatment was more significant than dose. Surprisingly, ICV PPS treatment had intermediate effects on most of these brain markers, perhaps due to the limited dose and/or duration of treatment. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Alternatively, it may be able to exert an effect just through reducing peripheral cytokine levels (Guo et al . ).…”
Section: Anti‐inflammatory Treatments In Mpsmentioning
confidence: 97%
“…Alternatively, it may be able to exert an effect just through reducing peripheral cytokine levels (Guo et al . ).…”
Section: Anti‐inflammatory Treatments In Mpsmentioning
confidence: 97%
“…Glycosaminoglycan (GAG) storage, which induces a complex sequence of molecular changes leading to inflammation, synovial hyperplasia, and cartilage apoptosis [ 8 ], is assumed to play a major role in joint and bone pathologies in MPS diseases. Animal and human studies investigating the treatment effects of anti-inflammatory drugs such as pentosan polysulfate (PPS) on skeletal pathologies in MPS III are under investigation [ 21 ]. In addition to inflammation, many studies in various MPS animal models have reported early abnormalities of chondrocyte organization in the growth plate and architecture of cortical bone which could be a trigger for abnormal bone modeling and remodeling leading to secondary hip deformities [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory effects of PPS have been extensively documented, and broad anti-inflammatory effects were previously studied in three MPS animal models [52][53][54]56], and also in cells from Fabry and Gaucher disease patients treated with PPS [55]. Several cytokines related to inflammation were also measured during the current trial.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various experimental therapies being studied in MPS, PPS is somewhat unique since it not only reduces GAG storage but also significantly reduces inflammatory cytokines in MPS animal models. It also appears to cross the blood-brain barrier, although this has only been studied in the context of one neurological MPS model (MPS IIIA) [56]. There is extensive clinical data in different diseases showing the safety of PPS administration in humans, and now seven MPS patients of two different types have been treated (4 MPS I and 3 MPS II) without serious, drug-related adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation